Antioxidant properties of crude extract, partition extract, and fermented medium of Dendrobium sabin flower - Abu, Farahziela; Mat Taib, Che Norma; Mohd Moklas, Mohamad Aris; Mohd Akhir, Sobri (Hindawi Publishing Corporation, 2017)
Antioxidant properties of crude extract, partition extract, and fermented medium from Dendrobium sabin (DS) flower were investigated. The oven-dried DS flower was extracted using 100% methanol (w/v), 100% ethanol (w/v), and 100% water (w/v). The 100% methanolic crude extract showed the highest total phenolic content (40.33 ± mg GAE/g extract) and the best antioxidant properties as shown by DPPH, ABTS, and FRAP assays. A correlation relationship between antioxidant activity and total phenolic content showed that phenolic compounds were the dominant antioxidant components in this flower extract. The microbial fermentation on DS flower medium showed a potential in increasing the phenolic content and DPPH scavenging activity. The TPC of final fermented medium showed approximately 18% increment, while the DPPH of fermented medium increased significantly to approximately 80% at the end of the fermentation. Dendrobium sabin (DS) flower showed very good potential properties of antioxidant in crude extract and partition extract as well as better antioxidant activity in the flower fermented medium.